«I prepare my rotation by», a virtual complement of paediatric specialist training - Francisco Hijano Bandera; Javier González de Dios; M. Rosa Pavo García; Esteban Peiró Molina; Carmen Villaizán Pérez; Carlos Ochoa Sangrador; M. José Mellado Peña (Elsevier, 2019)
The Spanish Association of Paediatric (AEP) has, among its objectives, to develop activities aimed at the training of its members. Thus, in 2013, it began its most ambitious training project, the virtual platform, "Continuum". Now it presents a new section aimed at Internal Medicine Residents (MIR) in Paediatrics and their tutors: "I Prepare My Rotation By"-PMRP, which has as objectives to reduce the variation in MIR training, to help the tutors in their teaching function, to facilitate collaborative and skill-based learning, reflective training, and the resolving of the particular problems of the professional profile of each paediatric speciality.PMRP is split into three main sections: "From where do we start" (with the sub-sections: self-assessment questionnaire and learning agreement), "Situations to resolve" (where the clinical scenarios that have been selected in the learning agreement are broken down), and "To where have we got" (which includes again the sub-sections at the beginning of the rotation in order to check if the expected objectives have been reached, and the assessment report). It also has other resources: prior knowledge, portfolio, and discussion forum.Five features of the proposed training model should be highlighted: the clinical scenario as a starting point; skill-based learning (based on the Global Paediatric Educational Consortium); the assessment as a training stimulus; the power of collaborative learning, and the participation of the different specialist societies of the AEP in the development of its contents. Resumen: La Asociación Española de Pediatría (AEP) tiene entre sus objetivos desarrollar actividades encaminadas a la formación de sus socios. Así, en 2013 puso en marcha su proyecto formativo más ambicioso, la plataforma de formación virtual, "Continuum". Se presenta ahora una nueva sección dirigida a los Médicos Internos Residentes (MIR) en Pediatría y a sus tutores: "Preparo Mi Rotación Por"- PMRP -, que tiene como propósitos disminuir la variabilidad en la formación de los MIR, asistir a los tutores en su función docente, facilitar el aprendizaje colaborativo y basado en competencias, el entrenamiento reflexivo y la resolución de problemas propios del perfil profesional de cada especialidad pediátrica.PMRP se distribuye en tres secciones principales: "De dónde partimos" (con las subsecciones: cuestionario de autoevaluación y contrato de aprendizaje), "Situaciones a resolver" (donde se desglosan los escenarios clínicos que han sido escogidos en el contrato de aprendizaje) y "A dónde llegamos" (que vuelve a incluir las subsecciones del comienzo de la rotación, para comprobar si los objetivos previstos han sido alcanzados, y el informe de evaluación). Además, cuenta con otros recursos: conocimientos previos, porfolio y foro de debate.Cabe destacar cinco aspectos del modelo formativo propuesto esta nueva sección: el escenario clínico como punto de partida; el aprendizaje basado en competencias (fundamentado en el Global Pediatric Educational Consortium); la evaluación como estímulo de formación; el poder del aprendizaje colaborativo y la participación de las diferentes sociedades de especialidad de la AEP en el desarrollo de sus contenidos.